PENGGUNAAN KATETER INTRAPLEURA (WATER SEALED DRAINAGE, INDWELLING PLEURAL CATHETER, PIGTAIL CATHETER) PADA PENATALAKSANAAN KANKER PARU DENGAN EFUSI PLEURA MASIF - Tamam Anugrah TAMSIL; Elisna SYAHRUDDIN; Dicky SOEHARDIMAN (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2019)
Massive pleural effusion is one of the problems in lung cancer treatment that cause death. The main treatment of cancer patient with massive pleural effusion is the placement of intrapleural catheter. This is a preliminary study which is aimed to assess tolerancies and efficacies of intrapleural catheter (WSD, IPC or pigtail catheter) in lung cancer with massive pleural effusion. This study is a retroscpective observational cohort study. Subjects are lung cancer patients with massive pleural effusion and catheterized with intrapleural catheter (WSD, IPC or pigtail catheter). The datas were taken from medical record at RSUP Persahabatan and assessed for tolerancies (acute or late complication) and efficacies ((length of hospital admission after catheter placement, duration and the reason of retraction) of intrapleural catheter. Tolerancies and efficacies of intrapleural catheter (WSD, IPC or pigtail catheter) in lung cancer patients with massive pleural effusion are quite good and safe. Prospective cohort studies are needed in the future to determine which type of intrapleural catheter is better for the treatment of massive pleural effusion in lung cancer patients.